Understanding Wealth Inequalities in Education Access in Urbanizing Sub-Saharan Africa - Mutisya, Maurice; Muchira, John Munyui; Abuya, Benta A. (Frontiers in Education, 2021)
Introduction: Urbanization is a double-edged sword, while it is transforming the world, it is also creating spaces that pose threats to its benefits. In sub-Saharan Africa, urbanization is occurring amidst slowed economic growth and into spaces that are already strained. This is resulting in the growth of urban poverty and possibly increasing inequalities. It is thus imperative to understand the effects of urbanization in realizing inclusive and equitable education for all. Objective: We examine inequalities in enrolment of schooling going children aged 6 to 17 years living in urban areas using the latest Demographic and Health Surveys data from 24 SSA countries. Methods: We utilize three measures of inequality: Rate difference, rate ratio, and relative concentration index to examine inequalities in education access. Using wealth status as the key inequality indicator, we compute and compare school enrollment of children living in urban poor households with that of those living in urban rich households for each measure of inequality. Where appropriate, we stratify the results by country, age, and gender. Results: The results show high levels of inequalities in education access in urban settings. Across all the measures of inequality, in most countries, children from urban poor households were significantly less likely to be in school compared to those from the richest ranked households. The degree of inequality varied considerably between countries and the age groups. Among children aged 6 to 11 years, Tanzania, Burundi, Nigeria, and Uganda had the highest degree of inequality favouring the urban rich. We also find intriguing results in few countries such as Ethiopia, Benin, Senegal and Mali, which the urban poor had, better school enrolments than the urban rich. We do not find a clear pattern to suggest girls from poor households are overly disadvantaged than boys from similar households. Conclusion: Our study shows a high level of inequalities in education access in an urban setting, with children age in urban poor settings hugely disadvantaged. There is a need for strategic efforts –in terms of deliberate interventions and policy frameworks - to combat the apparent inequalities that disadvantage children from poor families from accessing education.